The Current Role of Woodman#x2019;s Arytenoidectomy in Treating Bilateral Abductor Vocal Cord Palsy (Global Journal of Medical Research, 2019)
Bilateral abductor vocal cord palsy is one of the most complex laryngeal condition which an otolaryngologist do encounter in their routine practice. Complexity because of the various etiological factors which can affect neurological component anywhere from cerebral cortex to superior mediastinum or local factors like cricoarytenoid fixation. The treatment option is to establish the airway without compromising the voice and lower airway protection from aspiration. Various surgical options have evolved in due course of time ranging from open procedures to laser endoscopic procedures. Objectives: Evaluating the role external arytenoidectomy (woodman#x2019;s) in the treatment of bilateral abductor vocal cord paralysis. Materials and methods: It#x2019;s a retrospective study including 15 cases of bilateral abductor vocal cord palsy of various etiologies varying from congenital to iatrogenic ones.
Keywords: bilateral abductor vocal cord palsy (bavcp); woodman#x2019; s arytenoidectomy; laterofixation; vocal fold immobility